Evaluation of the Arabic language book for the third intermediate grade in the light of the foundations of sustainable development (Journal of Misan Researches, 2022)
The current study aims to "evaluate the Arabic language book for the third intermediate grade in light of the foundations of sustainable development", and this was done by answering the following question: What is the availability of the foundations of sustainable development in the Arabic language book for the third intermediate grade? The researcher adopted the descriptive-analytical approach, and the research community was limited to the content of the Arabic language book for the third intermediate grade, c1, c2, and third edition for the academic year 2021 AD. To ensure the validity of the tool, it was presented to a number of experts specialized in teaching methods, measurement, valuation, and psychology. The researcher calculated the reliability of the research tool by means of stability over time and the objectivity of correction, where the reliability coefficient reached (0.85). 56) Paragraph. The researcher used the arithmetic mean, percentages, and Pearson correlation coefficient to process the data, as the results resulted in a disparity in the distribution of the sub-dimensions of sustainable development available in the content of the Arabic language book, where the social dimension came in first place with (162) recurrence of representative indicators In our book under research, with a percentage of (66.12%) about the rest of the dimensions of sustainable development represented in the book, And in the second place, the economic dimension came at a rate of (61) iterations at a rate of (24.89%), and in the last place came to the environmental dimension at a rate of (22) iterations and at a rate of (8.97%). Sustainable development to contribute to the process of analysis and development of the textbook, and the need to take care of writing the Arabic language book according to the dimensions of sustainable development and its equal representation and for all dimensions of sustainable development, including economic and environmental.